2023
DOI: 10.3390/app13031817
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Seismic Demands on Non-Structural Components Attached to Reinforced Concrete Frames

Abstract: Nonstructural components (NSCs) are the systems that are attached to the floors of a building structure. NSCs have become critical in sustaining post-earthquake functionality while constructing seismic-resilient structures. The seismic behavior of the NSCs primarily depends upon the behavior of the structure to which the NSC is attached. Building structures are subjected to earthquake loads and behave differently when the supporting soil type varies. In light of this, this study investigates the seismic demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…4, it can be observed that the two peaks observed in the elastic and inelastic FRS are recorded close to the structure's elastic and inelastic modal periods (Table 3), respectively. This finding from this study is consistent with the outcomes of the previous research [11][12][13]. The Floor Response Spectra (FRS) exhibit a consistent trend of increasing magnitude from the first floor at the bottom to the third floor at the top.…”
Section: Floor Response Spectrum (Frs)supporting
confidence: 93%
See 1 more Smart Citation
“…4, it can be observed that the two peaks observed in the elastic and inelastic FRS are recorded close to the structure's elastic and inelastic modal periods (Table 3), respectively. This finding from this study is consistent with the outcomes of the previous research [11][12][13]. The Floor Response Spectra (FRS) exhibit a consistent trend of increasing magnitude from the first floor at the bottom to the third floor at the top.…”
Section: Floor Response Spectrum (Frs)supporting
confidence: 93%
“…The floor response spectrum (FRS) method is an analytical approach that operates by separating various considerations [7][8][9][10][11][12][13]. Initially, the primary structure undergoes dynamic analysis independently, without factoring in the secondary system's influence.…”
Section: Introductionmentioning
confidence: 99%
“…Biological neural networks function as simplified constructs that offer an analytical depiction of artificial neural networks (ANNs). With their ability to handle large datasets, tackle complex problems, and navigate ambiguous situations, neural networks have proven to be more accurate tools for calculations and predictions compared to conventional computational methods [75][76][77][78]. The primary challenge in constructing this model lies in determining the optimal architecture, including the number of hidden layers, epochs, batch size, and more.…”
Section: Ann Model's Architecture and Hyperparameter Tuningmentioning
confidence: 99%
“…The component dynamic amplification factor is represented by the ratio FRS/PFA (CDAF). Understanding the seismic behaviour of non-structural components requires knowledge of the CDAF [12,13]. Figure 3 shows the CDAF spectra for different primary structural periods for a 5% damping ratio of the NSC.…”
Section: Component Dynamic Amplification Factormentioning
confidence: 99%
“…To do this, it is necessary to calculate the floor response spectrum (FRS) at the location where the NSC is connected to the main system. *Corresponding Author Email: noroozinejad@kgut.ac.ir (E. Noroozinejad Farsangi) Using a decoupled analysis method, the floor response spectrum (FRS) approach, is used [7][8][9][10][11][12][13][14][15]. Without considering the impact of the secondary system, the fundamental structure is dynamically analyzed first.…”
Section: Introductionmentioning
confidence: 99%